On active layer processes and landforms in western Dronning Maud Land, Antarctica - Scott, David Alan (Rhodes University, Faculty of Science, Department of Geography, 2015)
Permafrost is a variable in Antarctic terrestrial ecosystems, and the role it plays in the cryosphere is not well understood. There is much still to be learnt about the thermal state, physical properties, thickness and age of permafrost in Western Dronning Maud Land (WDML). Active layer dynamics and observed change over time have the potential to improve our knowledge of climate change. Understanding the effects of a warming climate on permafrost can also be of benefit to infrastructure, especially in areas with a large amount of frozen ground such as Scandinavia, Canada and Russia. Active layer and permafrost dynamics of WDML, Antarctica, are presented and discussed using data from six study sites, namely the Robertskollen, Vesleskarvet, Flarjuven, Grunehogna, Slettjfell nunataks and the Troll research station in the Jutulsessen area. Ground and ambient air temperature, as well as ground moisture data were collected for each site. An inventory of active layer and permafrost landforms was compiled, as were the frequency of cycles over the zero-degree isotherm, and the depth of the active layer. Furthermore, 3D models, geo-referenced maps and Digital Elevation Models were created of study areas with the use of an Unmanned Aerial Vehicle (UAV). Polygonal features are the most common landscape feature and are common to most of the study sites. Robertskollen has the deepest active layer at over 66cm and Slettfjell the shallowest at 9cm. A maximum recorded air temperature of 8.76°C (10/11/2014) occurred at Troll with the second highest maximum of 6.77°C (22/12/2010) recorded at Vesleskarvet. Robertskollen has the highest observable biological growth and a maximum recorded ground temperature of 22.84°C (10/01/2014). Troll and Valterkulten, registered the second and third highest ground temperatures respectively. The high ground Temperature observed for Robertskollen may be ascribed to it being the lowest altitude site. The highest number of cycles over the zero-degree isotherm was observed at Troll (11.01%), followed by Robertskollen (10.99%). For relatively warm areas, such as Robertskollen it is recommended that two metre borehole loggers are installed in order to capture a detailed understanding of the active layer. The UAV proved to be a beneficial tool for capturing aerial photographs for post fieldwork analysis and 3D modelling.
Keywords: Landforms -- Antarctica -- Queen Maud Land; Permafrost -- Antarctica -- Queen Maud Land; Permafrost -- Thermal properties -- Antarctica -- Queen Maud Land; Climatic changes -- Antarctica -- Queen Maud Land; Cryosphere; Drone aircraft -- Antarctica -- Queen Maud Land; 3-D modeling